Cost-benefit analysis of energy transmission projects : a case study of coal transport versus electricity transmission in China - Dong, Jian-jing; Zhai Youg-Ping; Edelman, David J.; Dang, G. V.; Government of Denmark (Bangkok : Asian Institute of Technology, 1991)
This study describes a methodology for economic analysis of alternatives of coal transportation versus electricity transmission in China. Fundamental principles from theoretical considerations for developing this methodology are also included. This methodology is based on the decision criteria of project economics. The main decision criteria are Net Present Value, Internal Rate of Return and Cost-benefit Ratio. A cost-benefit analysis of alternatives of siting energy facility has been carried out based on available data from China for finding out the optimum al tern a ti ve of energy resource transmission. Both financial and economic evaluation are implemented. The environment impact with a energy project ls considered due to different location of power plant. The economic benefit of an integrated power pool with the project of electric power transmission has been added to electricity transmission alternatives. Under fundamental assumptions, the conclusion suggests that electricity transmission project is favored in the study area according to the synthetic comparison and analysis.
A thesis study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Environment, Resources and Development
Thesis (M.Eng.) - Asian Institute of Technology, 1991
Keywords: Power transmission; Cost effectiveness